Eksplorasi Dialektis Nilai Pendidikan Karakter Hindu dalam Narasi Kritis Geguritan Pan Bungkling - Luwih, I Made (Jayapangus Press, 2026)
Character education in Indonesia currently faces serious challenges in the form of moral degradation and the ineffectiveness of learning models that tend to be normative and under-emphasize critical reasoning. This study aims to explore Geguritan Pan Bungkling as an alternative source of character education based on inquiry and critical dialectics, an approach that shifts from the study of heroic texts that emphasize passive acceptance. This study uses a qualitative descriptive method with a dialectical hermeneutic approach and content analysis to dissect the textual and contextual meaning of the classic Geguritan Pan Bungkling manuscript. The results show that the character of Pan Bungkling represents the integration of theological intelligence (Pradnyan) that uses critical reasoning to question ritual formalism and systematically actualizes the values ​​of Pancasatya and Tri Hita Karana through leadership strategies (Niti) and a spirit of national defense in the face of conflict. It concludes that this study offers a strategic ethnopedagogical solution that transcends dogmatism, utilizing satire and paradox as effective media for shaping the character of a young generation that is intelligent, tolerant, and possesses high integrity.